Leading the way into the future: the development of a (lead) market for care robotics in Japan. (1st January 2015) - Kohlbacher, Florian; Rabe, Benjamin
Japan is an ideal country for studying the effects of demographic change and population ageing. This paper focuses on an ongoing market creation process for innovative technologies such as care robotics in Japan. The labour market situation in the Japanese healthcare market is worsening, and this is why some creative inventors and entrepreneurs try to develop technologies that can (1) enable aged persons to continue living independently in their usual environment and (2) improve processes in care facilities. Combining lead market theory, stakeholder theory and the literature on market emergence, we analyse two case studies involving the most notable developments in care robotics in Japan: the HAL robot suit and the therapeutic robot Paro. We identify the stakeholders in the market creation process of Japanese care robots and evaluate the lead market potential of this developing sector. The acceptance of such robotic technologies will also be discussed with reference to the cultural specifics of Japan and other countries.